LITERASI KEUANGAN YANG MEMPENGARUHI CASHLESS PAYMENT USAGE TERHADAP INKLUSI KEUANGAN DI DKI JAKARTA - Parulian, Ronald; Junianty, Emmy; Harianja, Elma (Universitas 17 Agustus 1945 Jakarta, 2025)
Non-cash payments have a big influence on financial inclusion where technology users are made easier by the existence of E-Wallets in the form of Shopee Pay, GoPay, OVO, LinkAja, Dana and several other E-Wallets supported by certain banks. This research aims to measure how much influence Cashless Payment is used in the financial management of the people of DKI Jakarta. This research also discusses how many people use cashless payment methods in DKI Jakarta along with regular data calculations. Using E-Wallet in Cashless also offers convenience in carrying out the buying and selling process. Apart from that, it also really helps buyers no longer wait when there is a refund. Cashless transactions are increasing every year due to the use of technology which is increasingly being used by the wider community and is also becoming more easily accessible in all areas of DKI Jakarta.